2012
DOI: 10.1136/bmj.e4260
|View full text |Cite
|
Sign up to set email alerts
|

Risk of pneumonia associated with use of angiotensin converting enzyme inhibitors and angiotensin receptor blockers: systematic review and meta-analysis

Abstract: Objective To systematically review longitudinal studies evaluating use of angiotensin converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) and risk of pneumonia.Design Systematic review and meta-analysis.Data sources Medline through PubMed, Web of Science with conference proceedings (inception to June 2011), and US Food and Drug Administration website (June 2011). Systematic reviews and references of retrieved articles were also searched.Study selection Two reviewers independently selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
195
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(224 citation statements)
references
References 96 publications
8
195
1
9
Order By: Relevance
“…Consequently, referring to the ability of SP to enhance protective reflexes, ACE inhibitor treatment has been discussed as a possible strategy to reduce aspiration after stroke [47]. Interestingly, in line with this reasoning, two Asian observational studies found reduced pneumonia rates in hypertensive stroke patients treated with ACE inhibitors in comparison to patients managed with other antihypertensive drugs [48, 49], a conclusion that was also uphold in a meta-analysis [50, 51]. However, in more recent trials, this assumption was decisively questioned with two case-control studies and one randomized-controlled trial failing to show any evidence of a putative protective role of ACE inhibitors in dysphagic stroke and non-stroke patients [52-54].…”
Section: Discussionmentioning
confidence: 59%
“…Consequently, referring to the ability of SP to enhance protective reflexes, ACE inhibitor treatment has been discussed as a possible strategy to reduce aspiration after stroke [47]. Interestingly, in line with this reasoning, two Asian observational studies found reduced pneumonia rates in hypertensive stroke patients treated with ACE inhibitors in comparison to patients managed with other antihypertensive drugs [48, 49], a conclusion that was also uphold in a meta-analysis [50, 51]. However, in more recent trials, this assumption was decisively questioned with two case-control studies and one randomized-controlled trial failing to show any evidence of a putative protective role of ACE inhibitors in dysphagic stroke and non-stroke patients [52-54].…”
Section: Discussionmentioning
confidence: 59%
“…Proposed mechanisms of action behind these associations are interference with aspiration and cough induction through ACE inhibition [3], immunomodulation by statins, and gastrointestinal bacteria overgrowth due to increased stomach pH by proton pump inhibition. Recent reviews and meta-analyses of ACEi and CAP [4], statins and CAP [5,6], as well as PPI and CAP [7] show a marked heterogeneity in findings. In these reviews, the most often mentioned explanation for differences in findings is unmeasured confounding in some or all of the studies reviewed.…”
Section: Introductionmentioning
confidence: 95%
“…First, as all observational studies, we cannot rule out the possibility that additional baseline variable (unmeasured confounders) might have some impact on the development of in-hospital SAP after AIS, such as use of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers. 44 Second, the time course of SAP after AIS is unclear. Because we only have information on new-onset SAP during hospitalization without documentation of the exact date, our data allow no conclusion as to whether patients with a longer length of stay per se are more likely to develop pneumonia or whether diagnosis of pneumonia leads to a longer hospitalization.…”
Section: May 2013mentioning
confidence: 99%